Intervention in a ministry - Foladori, Horacio; Sepúlveda, Livia (Revista de Psicología, 1999)
This paper shows an intervention based on the institutional analysis theory, done in a section of a Secretary. The report includes the analysis of the demand, the contract, the methodology, the techniques used and de movement of the group work through the different conflicts related to burocracy, that arrows in ist way. At last, some conclusions and recommendations to the authorities are indicated.